2016
DOI: 10.1038/nclimate3146
|View full text |Cite
|
Sign up to set email alerts
|

Amplified plant turnover in response to climate change forecast by Late Quaternary records

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
0
31
1
Order By: Relevance
“…Our findings contrast with other studies, such as those of Nogues‐Bravo et al (), who found a strong reduction of range loss when including fossil data for projecting future conservation risks for plants in North America and Europe. Such qualitatively different responses to incorporating fossil data could have many explanations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings contrast with other studies, such as those of Nogues‐Bravo et al (), who found a strong reduction of range loss when including fossil data for projecting future conservation risks for plants in North America and Europe. Such qualitatively different responses to incorporating fossil data could have many explanations.…”
Section: Discussioncontrasting
confidence: 99%
“…Such qualitatively different responses to incorporating fossil data could have many explanations. The results of Nogues‐Bravo et al () might have been influenced by their grouping of species into genera and families, whereas we studied responses at the species level for six of our eight plant taxa. Alternatively, these differences might also be attributable to inherent differences of temperate and tropical species.…”
Section: Discussionmentioning
confidence: 99%
“…Several avenues exist to improve ecological forecasting in the face of climate novelty. One is to pool ecological data from multiple time periods to better encompass the climatic niche of species (Nogués‐Bravo et al., ), with a critical need to focus on past warm periods that may be partial analogs for warm future climates. How best to pool data through time to avoid biasing models to particular time periods is a subject of ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, our results are not consistent with the hypothesis that extinctions occurred commonly in areas of high climate velocity (in geological terms) because species in those areas failed to track shifting climatic conditions (Sandel et al, ). It is likely that biological responses to post‐glacial climate changes are primarily through changes in species abundance and distributions (Nogués‐Bravo et al, ), rather than through massive extinctions of species. Small populations of at least some long‐lived species may have persisted in refugia through periods of adverse climatic conditions (Willis & MacDonald, ).…”
Section: Discussionmentioning
confidence: 99%